PENGARUH MODEL TALKING STICK TERHADAP HASIL BELAJAR SENI BUDAYA DI SMA - Hairusanti, Famela; Wartiningsih, Agus; ismunandar, ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe how much influence the application of the talking stick to the study of students learning Cultural Arts in Class X State Senior High School 5 Pontianak. The method used is the method of quasi experiment with the design of the study is Nonequevalent Control Group Design. The sample in this study is 84 students. Results of the data analysis indicate that the learning outcomes of students at the post-test in the experimental class effect of 0.88. This means learning by applying the model Talking Stick give effect to the high criteria for the study of students in grade X in learning Cultural Arts in State Senior High School 5 Pontianak .Keywords: Influence, cooperative learning model of talking stick, Learning Outcomes.Â